PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS-ACHIEVEMENT DIVISIONS (STAD) PADA MATA KULIAHILMU LINGKUNGAN SEBAGAI UPAYA MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR MAHASISWA PRODI PENDIDIKAN IPA FKIP UST TAHUN AKADEMIK 2010/2011 - Tias Ernawati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
This research has been done to know how STAD as a model of study could increase activity and achievement the students of natural science education department on 2010/2011 of academic year and also to know the statement according to the model. This research was begun on observing class condition to identify problems. This was a class action research which had cycles to improve class condition. Each cycle was consist of planning, doing and observing, reflecting. Planning action used STAD model. The model included announcing model’s aim, studying college’s topics, grouping, tasking of groups, individual evaluating and rewarding the winner group. The winner was the most of points. Total points were equals of discuss point and average of total individual evaluating points in group. The instruments of this research were lecture-observing papers, students-observing papers, evaluating papers and statements papers.The research’s result showed increasing of students’ activity. At first discussion on first cycles, there were 38.7% students active, at last discussion on second cycles there were 90.3% students active. Average of students’ achievement has increased 20.6 points, i.e. from 61.8 to 82.4. According to the students’ statements of model showed that they liked STAD because they could get the topics easier and improve students’ activity by making life-class in order to increase achievement.